Dimensi Filsafat dalam Pengelolaan Sumber Daya Alam: Kajian Peran Manusia dalam Menjaga Keseimbangan Lingkungan - Lora Santika; Muhammad Sarjan (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
The global environmental crisis—marked by deforestation, land degradation, pollution, and climate change—is a consequence of unsustainable natural resource (NR) exploitation. Population growth and the dominance of pragmatic economic paradigms are key drivers of environmental destruction. This article examines the role of philosophy in NR management as an alternative approach that is more ethical and sustainable. Using a literature review method, this study analyzes environmental philosophical perspectives—particularly anthropocentric, biocentric, and ecocentric ethics—and their relevance in shaping policies and ecological awareness. The findings show that integrating philosophical values can foster moral awareness toward nature, strengthen justice-based environmental policies, and support holistic development approaches. The study also highlights failures in NR management due to ethical crises, such as overfishing in Indonesian waters and deforestation linked to food estate projects. Community-based management models and local wisdom—such as sasi and subak systems—are shown to be more aligned with ecocentric and sustainable principles. Therefore, a paradigm shift is needed—from an exploitative approach to a philosophical one that sees humans as part of, not rulers over, ecosystems. Integrating philosophy into NR management is not only essential for environmental preservation but also for ensuring the sustainability of future generations.